PENGARUH DESAIN INTERIOR TERHADAP MINAT PENGUNJUNG DI MARRIOTT HOTEL HARBOUR BAY KOTA BATAM - Dailami; Moh. Thandzir; Haufi Sukmamedian; Nensi Lapotulo (JURNAL MATA PARIWISATA, 2023)
Interior design is all about aesthetic value as well as providing comfort and appeal to visitors. In addition to increasing the attractiveness of visitors, the interior and layout arrangement can also increase the value of the existence of the place. The appearance and layout are important in creating a comfortable room and can also affect the mood, views and interest of buyers to visit the place. This study was made with the aim of describing the effect of interior design and layout on consumer attractiveness at Anchor Cafe & Roastery Batam. The method used by the researcher is a quantitative method.